the regional city - P e t e r C a l t h o r p e , w i l l i a m f u l t o n (island press, 2001)
This book takes up the challenge of the Regional City as the necessary scale on which to confront our societyâ€™s economic, ecological, and social problems. Calthorpe and Fulton have gotten past those twin towers of negativismâ€”the urban crisis and suburban sprawlâ€”to provide a manifesto for all those who see traffic jams, loss of open space, and racial divisions not as necessities to be endured but as problems to be solved. Among recent works on regionalism, this book, in my opinion, is the most comprehensive, the most practical, and the most visionary. As Calthorpe and Fulton announce, the Regional City is â€œnot merely a theory,â€ and they back up this claim with a wonderfully comprehensive selection of project descriptions and graphics from Calthorpe Associatesâ€™ work. Their discussion of these projects is supported by Calthorpeâ€™s practical, hands-on experience in so many of our most creative and important regional initiatives. Perhaps most crucially, this book is visionary in the sense that the authors insist that an overall regional design vision is necessary for successful action. For Calthorpe and Fulton, regionalism means not only thinking bigger but thinking better. It means seeing the interconnections between, for example, land use and transportation, open space and public space, growth boundaries at the edge of the region and rebuilt inner cities at their core. Where traditional policy analyses tend to separate and obscure these key interconnections, physical design embodies and reveals the links. It provides the common ground around which the different stakeholders in the region can come together for effective action. This book is a powerful argument for the crucial role of regional design as the synthetic discipline bringing together the separate worlds of economics, ecology, social policy, and aesthetics. The Regional City is therefore filled with designs for the present and the future, but it is also based on a long tradition of American regional thought and planning. A brief comparison between Calthorpe and Fulton and some of their predecessors might help us to understand how this book is both a critique of and a contribution to that tradition. As early as the 1920s, a remarkable group of architects, planners, and social activists led by Lewis Mumford, Clarence Stein, Henry Wright, and Benton MacKaye had attempted to make the region the primary focus for American planning